Efficiency parameters of Asynchronous Transfer Mode networks equipment maintenance - Конахович, Г. Ф.; Сухопара, О. М.; Потапов, В. Г. (Proceedings of National Aviation University (archive), 2021)
The substantiation of a selection of efficiency parameters of Asynchronous Transfer Mode equipment maintenance is executed that has essential practical interest in connection with wide application of this equipment in modern global transport networks.